ANALISIS MATERIAL ROLLER CVT RACING UNTUK PENINGKATAN PERFORMA SEPEDA MOTOR HONDA BEAT 110CC - Agung Maulana Rahmat; Dede Ardi Rajab; Nefli Yusuf; Amri Abdulah (Jurnal Teknologika, 2022)
Abstrack In the industry, most do not use pure aluminum material, but utilize material absorption. An alloy that is often used in the foundry industry is Al-Si. The smelting process using a tool made of refractory stone as a heat insulator is able to increase the heat in the combustion chamber to 1,000 °C, the melted metal material must be at a melting point below 1,000 °C, such as aluminum, brass, lead and so on,. Roller is one of the components contained in the automatic transmission or CVT. Roller bar functions to press against the inner wall of the primary pulley during high rotation. This racing roller is a roller that is usually used to improve the performance of an automatic motorcycle. Rollers are heavy force balance bearings that are useful for pressing the inner walls of the primary pulley during high revolutions. Based on the results of the discussion in this study that the hardness value at three different points and has been carried out as much as 3 times for one test material, namely the Standard Roller, that data 1 average hardness price of 86 with an average penetration depth of 0.12 mm, for data 2 the average hardness price of 93 with an average penetration depth of 0.28 mm. Keywords : Material, Roller, and Hardness Tester.